Workload Analysis in Quantity Optimization Labor Using FTE And RSME Methods in the Packaging Department of a Pharmaceutical Company - Ramadhan, Gilang; Hernadewita, Hernadewita (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2025)
Human Resources (HR) is one of the most important parts of a company, as the main driver to achieve company goals. The company requires a workload calculation to determine the workload received by its employees. The method used in this workload calculation is Full Time Equivalent and Rating Scale Mental Effort to calculate the workload received by employees of the solid packing department in each packaging process. The results of this study on the blistering, sleeving, IPC, sealing, and shippering processes are in the normal category with a workload value in the range of 1-1.28, while the cartoning process is in the overload category with a workload value of 1.60 . The results of the RSME value calculation on the blistering and sleeving processes get a weighting value in the range of 71-85 with a moderately large category, the IPC, sealing, and shipping processes get a weighting value in the range of 59-70 with a fairly large category, while the cartoning process gets a weighting value in the range of 86-100 with a large category. So it's necessary to add 1 employee so that the FTE value is distributed properly or the workload is normal and the RSME becomes fairly large.